An Analysis of Vocational School Goals Achievement: Case Study in West Java - Vidha Thaashaar, Julyestra; Ghazali, Achmad; Fauzi, Dani (Riviera Publishing, 2023)
Most secondary school students in developing countries have difficulty accessing higher Education after completing secondary Education, especially in Indonesia. The limited number of new job opportunities and the absence of a link and match between the competencies possessed by the workforce and employment have triggered the high Open Unemployment Rate (TPT) of VHS graduates, especially in West Java.This research uses mixed methods where data collection is carried out quantitatively and qualitatively. In collecting quantitative data, respondents to this study used data from 341 vocational students at six vocational schools in 5 districts/cities in West Java. Then strengthened by qualitative methods by conducting interviews. First, the thing that most influences the low quality of competitiveness of VHS students is that 21.07% of VHS students in West Java have a low VHS objective score. Second, the Quality of Education, Entrepreneurial Mindset, and Entrepreneurial Intentions simultaneously influence the goals of VHS in West Java Vocational School students, with an F count of 135,773 with a significance level of 0.000. Third, 54.7% of the goals of VHS students in West Java are influenced by the Quality of Education, Entrepreneurial Mindset, and Entrepreneurial Intentions. At the same time, 45.3% is influenced by other variables not analyzed in this study. to increase the competitiveness of VHS students, it is necessary to carry out various intervention efforts starting from the stages of input, process, output, and long-term results in the learning process in schools.